Menuntun Kodrat Anak: Refleksi Filosofis Pendidikan Ki Hadjar Dewantara dalam Membangun Karakter Siswa - Fanny Puspasari Sianipar; Syarifa Aini; Ema Linda Lumban Gaol; Amin Harahap (Pancasila and Civics Education Journal (PCEJ), 2026)
Abstract: Education in the era of digital transformation faces significant challenges in the form of the risk of cultural identity erosion and moral degradation among the younger generation. This study aims to re-explore the relevance of Ki Hadjar Dewantara's (KHD) philosophical thoughts in strengthening students' character, particularly through the Trisakti Jiwa concept and the Tringa method, and its implementation in the school environment. The method used in this study is a literature study with a qualitative descriptive approach contextualized within the educational ecosystem at SMA Negeri 1 Rantau Utara. The results show that effective character development rests on the harmonization of human internal potential, which includes the aspects of Cipta (intellectual), Rasa (emotional), and Karsa (determination). The process of internalizing these noble values is optimally achieved through the Tringa stages, namely Ngerti (cognitive understanding), Ngrasa (conscience appreciation), and Nglakoni (behavioral actualization). The conclusion of this study emphasizes that schools as